29. EVALUATION OF THE RESULT OF INTERTROCHANTERIC FRACTURE TREATMENT WITH PROXIMAL FEMORAL NAIL ANTI-ROTATION AT THONG NHAT DONG NAI GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Intertrochanteric fractures are quite common, accounting for 55% of proximal femur fractures, often occurring in the elderly, 2-3 times more common in women. Using the bone fixation technique with PFNA has many advantages. At our hospital, treatment intertrochanteric fractures with PFNA has been performed for many years. To evaluate our results, we conducted research:“Evaluation the result of intertrochanteric fracture treatment with proximal femoral nail antirotation at thong nhat dong nai general hospital”.Target:1. General objective: To evaluate the result of intertrochanteric fracture treatment with proximal femoral nail anti-rotation.2. Specific goals:- To determine the rate of accidents, complications, and treatment results.- Relationships to treatment results: Age, gender, fracture severity according to AO, surgery time.Research methods: Retrospective, prospective, descriptive series of cases.Research results: We operated and followed up 50 cases. With very good results, there were 13 cases (26%), good cases in 31 cases (62%), and an average of 5 cases (10%) with 1 case with bad results (2%). There were no cases of complications, 5 patients had joint stiffness (10%), 1 patient had cal deviation, joint stiffness and screw buds (2%), 40 patients had limb shortening (80%).Conclusion: Intertrochanteric fractures occured mainly in patients over 80 years old. Women account for more than men, the most common cause of injury was daily life accidents. The very good and good surgical results rate was at 88%. There was no relationship between age, gender, AO classification and surgery time of study participants with the results of treatment of intertrochanteric fractures.
Keywords: Proximal femoral nail anti-rotation (PFNA), intertrochanteric fracture.